How brand personality, brand identification and service quality influence service brand equity - Loureiro, S. M. C.; Lopes, R.; Kaufmann, H.R. (Cogent Business and Management, 2014)
During the past couple of decades, brand equity has emerged as one of the key concepts in marketing. Literature concerned with consumer brand relationship is calling for more studies in order to increase understanding of brand equity dimensions. Therefore, this study aims to contribute to the existing body of knowledge by examining the strength of relational variables on brand equity perceived by consumers. Findings support the proposed model in the service industry revealing that brand loyalty, brand identification, trust, brand personality and brand awareness are the variables that have a greatest impact on brand equity. Thus, this study is the first to measure the strength of assorted relational variables, and variables related with identification and personality on brand equity for brands in the service industry. In this vein, brand managers should be aware of the importance of building a brand regarding the way they communicate the features of the brand.